Effects of thickness difference and loading direction on fatigue properties of tailored welded blanks - Angelina, Lawrence (2013)
An approach to reduce manufacturing cost, weight, design and improve quality of a component is through the use of tailor welded blanks (TWBs). TWBs are welded blanks that consist of similar or dissimilar material, thicknesses, and surface properties before forming process. The purpose of the project is to evaluate the strength and fatigue behavior of the TWBs with different thickness combination and loading direction. The welding process was done by tungsten inert gas (TIG) arc welding. This study is divided into three parts. First, tensile tests were carried out. It was found that combinations were affected by the difference in thickness (2 mm/3 mm) and weld orientation (45o and 90o towards loading direction). The failure occurred in the middle of the weaker base metal parts. However, some of the joint specimens broke at the heat-affected zone. In addition, weld loading direction played a dominant role when the thickness difference was large. The second part investigates the effect of welding joint on the fatigue strength of the TWBs combination. The experimental results show that the failure occurs at welding zone as the specimens were subjected to fatigue and impact loading. In the last part of this thesis, the examination of the weld quality was carried out. Through the microstructure constituents in the weld, the strength and effects on the TWBs were discussed